Differences in Verbal and Visuospatial Forward and Backward Order Recall: A Review of the Literature - Donolato, Enrica; Giofrè, David; Mammarella, Irene C. (Frontiers in Psychology, 2017)
How sequential, verbal and visuospatial stimuli are encoded and stored in memory is not clear in cognitive psychology. Studies with order recall tasks, such as the digit and Corsi span, indicate that order of presentation is a crucial element for verbal memory, but not for visuospatial memory. This seems to be due to the different effects of forward and backward recall in verbal and visuospatial tasks. In verbal span tasks, performance is worse when recalling things in backward sequence rather than the original forward sequence. In contrast, when it comes to visuospatial tasks, performance is not always worse for a modified backward sequence. However, worse performance in backward visuospatial recall is evident in individuals with weak visuospatial abilities; such individuals perform worse in the backward version of visuospatial tasks than in the forward version. The main aim of the present review is to summarize findings on order recall in verbal and visuospatial materials by considering both cognitive and neural correlates. The results of this review will be considered in the light of the current models of WM, and will be used to make recommendations for future studies.